EFFECTIVENESS OF 25G COMPARED TO 27G QUINCKE SPINAL NEEDLE IN REGARD OF POST-DURAL PUNCTURE HEADACHE IN OBSTETRICS PATIENTS UNDERGOING SPINAL ANESTHESIA - KHALID , M; ASHFAQ , MA; OBAID , A; JAVED , HM; IQBAL , A; BUTT , MR (Biological and Clinical Sciences Research Journal, 2023)
Post-Dural puncture headache (PDPH) is a distressing complication that can occur following a dural puncture during spinal anesthesia. It is believed to arise from cerebrospinal fluid leakage and subsequent reflex cerebral vasodilation. Notably, PDPH occurs more frequently in young parturient women undergoing Caesarean sections. This study aims to evaluate the frequency of PDPH in patients undergoing elective Caesarean delivery, comparing the use of 25G and 27G Quincke spinal needles during spinal anesthesia. A randomized controlled trial was conducted at Aziz Bhatti Shaheed Teaching Hospital’s anesthesiology department in Gujrat from March 2022 to March 2023. A total of 140 parturient women with an American Society of Anesthesiologists (ASA) physical status classification of I to II, who underwent Caesarean sections, were included in the study. Exclusion criteria encompassed patients with infection at the injection site, severe hypervolemia, coagulopathy, increased intracranial pressure, severe aortic and mitral stenosis, severe preeclampsia, placenta previa grade–IV, placenta accreta, and twin pregnancy. The participants were divided into groups (Group I and Group II), each comprising 70 individuals. Spinal anesthesia was administered in the sitting posture using 25G Quincke spinal needles for Group I and 27G Quincke spinal needles for Group II. The puncture sites were the L3-4 or L4-5 intervertebral spaces. The incidence of PDPH was evaluated at 6, 12, 24, and 48 hours following the surgical procedure. Quantitative data, such as age, were presented as mean ± SD, while qualitative data were reported as frequency and percentages. Statistical significance was defined as a P-value < 0.05. The age range of the patients included in the study was 18 to 40 years. The mean age of patients in Group I was 26.12 ± 5.82 years, while in Group II, it was 26.34 ± 5.30 years. Eleven patients (15.71%) in Group I experienced PDPH, unlike three (4.28%) in Group II. The difference in PDPH incidence between the two groups was statistically significant (p = 0.031). Our findings indicate that using a 27G Quincke spinal needle for spinal anesthesia during Caesarean sections confers a distinct advantage in reducing PDPH occurrence compared to the 25G Quincke spinal needle. The results strongly support the superiority of the 27G Quincke spinal needle in minimizing the occurrence of PDPH.